Reduced acetylated α-tubulin in SPAST hereditary spastic paraplegia patient PBMCs - Wali, Gautam; Siow, Sue-Faye; Liyanage, Erandhi; Kumar, Kishore R.; Mackay-Sim, Alan; Sue, Carolyn M. (Frontiers in Neuroscience, 2023)
Hereditary spastic paraplegia is a neurodegenerative condition with no known curative treatment. There is an urgent need for biomarkers for use in therapeutic drug trials for HSP. Peripheral blood mononuclear cells (PBMCs) are an easily accessible source for biomarkers and are ideal for use in multi-center, international clinical trials. Noscapine, a tubulin binding drug, has previously been shown to restore acetylated α-tubulin levels in neuronal cells. In this study, we show that HSP-SPAST patient PBMCs have reduced levels of acetylated α-tubulin as previously seen in patient neuronal cells. Based on this finding, we propose further investigation of PBMC acetylated α-tubulin levels in clinical trials as a pharmacodynamic marker for noscapine treatment in patients with HSP-SPAST. We developed a high throughput assay that can measure acetylated α-tubulin levels in a large number of PBMC samples in a single assay run in order to avoid batch-to-batch variation, an important consideration for clinical trials. Noscapine is approved in several countries as an antitussive and makes a good candidate for re-purposing as a treatment of HSP. We show that oral noscapine crosses the blood brain barrier and increases the acetylated α-tubulin levels in mouse brain. We propose PBMC acetylated α-tubulin assessment as a potential pharmacodynamic biomarker for noscapine in future clinical trials.